2023
DOI: 10.1002/jat.4531
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology and safety study of L‐tryptophan and its impurities for use in broiler feed

Soo Min Ko,
Ji‐Eun Park,
Ji‐Young Lee
et al.

Abstract: L‐tryptophan has been utilized as a feed additive in animal nutrition to improve growth performance, as well as a dietary supplement to alleviate various emotional symptoms in humans. Despite its benefits, concerns regarding its safety arose following the outbreak of eosinophilia‐myalgia syndrome (EMS) among individuals who consumed L‐tryptophan. The causative material of EMS was determined to be not L‐tryptophan itself, but rather L‐tryptophan impurities resulting from a specific manufacturing process. To inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies in Sprague-Dawley rats and broiler chickens showed no adverse effects or EMS-related symptoms after L-tryptophan administration (Ko et al, 2022(Ko et al, , 2024. In a subchronic toxicity study using Sprague-Dawley rats, administration of L-tryptophan was revealed as safe up to 2000 mg/kg/day, with no significant differences between the control and treatment groups.…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies in Sprague-Dawley rats and broiler chickens showed no adverse effects or EMS-related symptoms after L-tryptophan administration (Ko et al, 2022(Ko et al, , 2024. In a subchronic toxicity study using Sprague-Dawley rats, administration of L-tryptophan was revealed as safe up to 2000 mg/kg/day, with no significant differences between the control and treatment groups.…”
Section: Introductionmentioning
confidence: 80%